SETTINGS COMPARISON ACTING PRESIDENT IN INDONESIA AND OTHER COUNTRIES THAT ADOPT A PRESIDENTIAL SYSTEM OF GOVERNMENT - Ilman Hadi; Irwan Triadi; Parluhutan Sagala (RADJA PUBLIKA, 2025)
This research aims to examine further regulations regarding the provisions of Article 8 paragraph 3 of the 1945 Constitution of the Republic of Indonesia. The Republic of Indonesia declares itself to be a legal state, which means that all aspects of the state must be based on the rule of law. On the other hand, the President of the Republic of Indonesia acts as both head of state and head of government, which indicates the nature of a presidential republic. Therefore, the position of President cannot be vacant because this position is so important and central. The research method used in this research is qualitative method with normative juridical analysis, namely explaining the legal norms that should be fulfilled (das sollen ) compared to the current situation (das sein). This research is also descriptive in nature, namely by describing the existence of a legal vacuum in the field of state administration, especially filling the position of interim president in Indonesia and its relationship with the threat of emergencies. The country's constitution regulates how to fill the vacancy in the presidential position in the event that the President and Vice President are permanently absent at the same time. However, this provision must be further regulated through laws and implementing regulations based on law. Twenty-two years have passed since the last amendment to the constitution but there is no legal regulation regarding this matter even though this situation is a threat and could result in a state of emergency status in the country. To facilitate the consideration and formulation of filling the position of president, the author presents a comparison with several countries so that it can be used which one is most suitable for the conditions of the Republic of Indonesia.